Commercially-driven lion part removal: what is the evidence from mortality records? - Coals, P; Dickman, A; Hunt, J; Grau, A; Mandisodza-Chikerema, R; Ikanda, D; Macdonald, D; Loveridge, A (Elsevier, 2020)
Trade-driven killing for body parts has long been a major cause of population decline for a number of big cat species. There are now worrying suggestions that commercialised illegal trade in body parts might become a threat for wild lions in Africa, and recent concerns have been raised that trade in captive-bred lion skeletons from South Africa may have stimulated demand for lion bones, claws, and teeth and thus incentivised commercially-driven, targeted poaching of wild lions for illegal trade. However, analysis of the prevalence of commercially-driven, targeted killing of lions for body parts is currently lacking for most major lion populations. In this study we make use of detailed, long-term records of mortality and body part removal from field sites in two of Africa’s lion population strongholds, the Hwange National Park and surrounds, Zimbabwe, within the Kavango Zambezi (KAZA) Transfrontier Conservation Area and the Ruaha landscape in Tanzania, to evaluate potential cases of commercially-driven part removal and targeted killings. We find no evidence of systemic targeted killing of lions for commercial trade at either site and suggest that the majority of part removals are opportunistic and culturally-driven. Nevertheless, we stress the requirement for vigilance around the issue of lion trade and support the development of further range-wide capacity to record wild lion mortality and body part removal data.